Mutations in the Filaggrin are Predisposing Factor in Korean Children With Atopic Dermatitis - Yu, Ho-Sung (The Korean Academy of Asthma, Allergy and Clinical Immunology; The Korean Academy of Pediatric Allergy and Respiratory Disease, 2013)
PURPOSE: Filaggrin (FLG) is a key protein that facilitates the terminal differentiation of the epidermis and the formation of the skin barrier. Recent studies showed that atopic dermatitis (AD) associates closely with loss-of-function mutations in the FLG gene. Asian and European populations differ in the frequencies of FLG mutations. Several FLG mutations, including 3321delA, E2422X, K4671X, S2554X, and R501X, occur frequently in Chinese and Japanese populations. The association between three FLG null mutations and AD in Korean children was investigated. METHODS: The FLG mutations in 1,430 children (aged 0-18 years) with AD and 862 control subjects were genotyped by using the TaqMan assay. RESULTS: The FLG null mutation E2422X was not detected in any patients with AD or control subjects. The R501X null mutation was detected in only one child with AD (0.1%). Children with AD had the 3321delA deletion significantly more frequently (2.4%) than the control subjects (0.0%, P<0.001). Children with AD also had a significantly higher combined allele frequency of the three FLG null mutations (2.6%) than the controls (0.0%, P<0.001). The 3321delA null mutation did not associate significantly with AD severity (P=0.842). When the patients with AD were divided into allergic AD and non-allergic AD patient groups, these two groups did not differ in terms of the frequency of 3321delA. CONCLUSIONS: The Korean children had a lower frequency of FLG mutations than European populations. FLG null mutations may be associated with the development of AD in Korean children.